2023
DOI: 10.1128/mbio.03028-22
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Dual Specificity of Sinorhizobium meliloti Clr, a cAMP and cGMP Receptor Protein

Abstract: Cyclic 3′,5′-AMP (cAMP) and cyclic 3′,5′-GMP (cGMP) are both long known as important nucleotide secondary messengers in eukaryotes. This is also the case for cAMP in prokaryotes, whereas a signaling role for cGMP in this domain of life has been recognized only recently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…A genome-wide ChIP-seq-based search for Clr–cAMP and Clr–cGMP binding sites identified over 800 genomic regions, largely overlapping between the both cNMPs. Consistent with ChIP-seq studies on CAP and CgrA, showing abundant low-affinity binding sites across the genome (Dong et al 2015 , Latif et al 2018 ), only a minor part of the identified Clr-bound DNA contained the Clr binding motif (Werel et al 2023 ), arguing for a conservation of this property of CRP proteins.…”
Section: α-Proteobacteriasupporting
confidence: 52%
See 3 more Smart Citations
“…A genome-wide ChIP-seq-based search for Clr–cAMP and Clr–cGMP binding sites identified over 800 genomic regions, largely overlapping between the both cNMPs. Consistent with ChIP-seq studies on CAP and CgrA, showing abundant low-affinity binding sites across the genome (Dong et al 2015 , Latif et al 2018 ), only a minor part of the identified Clr-bound DNA contained the Clr binding motif (Werel et al 2023 ), arguing for a conservation of this property of CRP proteins.…”
Section: α-Proteobacteriasupporting
confidence: 52%
“…The promoter regions of a fraction of the Clr-regulated genes contained sequences distantly resembling the CAP binding site. Electrophoretic mobility shift assays confirmed that DNA binding by Clr can be induced both by cAMP and cGMP, and promoter–reporter assays verified Clr-dependent transcription regulation by both cyclic nucleotides (Krol et al 2016 , Werel et al 2023 ). As determined by ITC analysis, Clr exhibited moderate preference for cAMP over cGMP, reflected by a higher affinity to cAMP (K d of 6–7 μM) than to cGMP (K d ∼24 μM) (Werel et al 2023 ).…”
Section: α-Proteobacteriamentioning
confidence: 88%
See 2 more Smart Citations
“…Likewise, the mycobacterial transcription factor DarR, which is regulated by c-di-AMP-binding, was found to be regulated as well through cAMP-binding (Schumacher et al 2023). Additionally, crosstalk between cyclic guanosine and adenosine second messengers is also known, as the CRP-Fnr transcription factors are known to bind both cAMP and cGMP, being only active in the cAMP-bound form in E. coli , while both cyclic nucleotides mediate the CRP activation in Sinorhizobium meliloti (Krol et al 2023; Werel et al 2023). Furthermore, both of cAMP and cGMP were found also to bind and modulate the activity of the AphA phosphatase in E. coli and Haemophilus influenzae (Kronborg & Zhang 2023).…”
Section: Figurementioning
confidence: 99%